Construction of SAPO-34/SiO2 composite: effective catalyst for methanol to olefins reaction. (6th August 2021) - Huang, Huiwen; He, Shanshan; Zhang, Qiang; Fan, Wenyang; Xu, Dongmei; Gao, Jun; Li, Chunyi
Abstract : The SAPO-34/SiO2 composite is superior to the SAPO-34–SiO2 catalyst in methanol conversion and product selectivity. Abstract : The strategy of in situ crystallization of SAPO-34 zeolite upon silica matrix was employed to construct the SAPO-34/SiO2 composite. The physicochemical properties of SAPO-34/SiO2 composite and its catalytic capability for methanol to olefins reaction were comprehensively compared to that of SAPO-34 zeolite and SAPO-34–SiO2 catalyst fabricated through a sol–gel method. The characterization results show that SAPO-34/SiO2 composite has good crystallinity, uniform crystal size, hierarchical pore structure, and moderate acidity. The introduction of silica matrix in the SAPO-34 shape-forming process makes SAPO-34–SiO2 catalyst and SAPO-34/SiO2 composite both conducive to the formation of ethene, but not conducive to the formation of propene. Compared to SAPO-34–SiO2 catalyst, SAPO-34/SiO2 composite exhibits better catalytic stability and light olefins selectivity in methanol to olefins reaction, which is attributed to its unique structure of SAPO-34 crystals adhered upon the surface of silica matrix.